The Analysis of Personal Characteristic in Corporate Culture and Work’s Productivity: Comparative Study of Accounting Staffs in Some Private Companies - Deasy Ariyanti Rahayuningsih (Jurnal Akuntansi dan Bisnis, 2007)
The purpose of this study is to examine the differences of gender and marital status (personal characteristic) in work‟s productivity and corporate culture. The data are collected through contact person from 145 accounting staffs of some private companies in Tangerang and Jakarta. Independent Sample-T test were used to test in each hypotheses. The results show that there is no difference between male and female in work‟s productivity and corporate culture, and there is a difference between marital status and single status in work‟s productivity and corporate culture.